Paul Krugman wants a quick end of the economic depression - Petre Prisecaru (Global Economic Observer)
In his book End This Depression Now! Paul Krugman tries to find some solutions to the lasting economic depression, mirrored by a low rate of growth and high level of unemployment. It is obvious that during the last three years (2010-2012) the economy of the most developed countries passed through a disappointing stagnation with a major contribution of austerity policies. But Keynes said that austerity had to be applied during the economic growth not when the economy was decreasing, and based on this idea Paul Krugman pleads for more government spending in order to support private sector and economic recovery.